Waste heat recovery from exhaust gas of an engine by using a phase change material. (2020) - Wahile, Ganesh S.; Malwe, Prateek D.; Kolhe, Ajay V.
Abstract: An increase in the economic rapid development worldwide creates a problem of shortage of energy and hence conservation of energy is the need of an hour. A recent survey shows that a considerable amount of energy is released in the form of waste heat from internal combustion engines which creates another issue of air pollution. According to the study, the conversion rate of energy supplied to an engine into useful power output that is mechanical work is around 30–40%. It means that the exhaust gases contribute to about 33% and engine cooling capacity about 30% to that of the energy supplied which results in an increase in entropy and other serious environmental problems. Indeed more and more energy should be converted into useful work. The present work consists of thermal energy storage from the exhaust gas of twin-cylinder four-stroke diesel engines with the help of sodium nitrate being used as the Phase Change Materials (PCM) and the energy available in exhaust gas without Phase Change Materials. The test of fuel used as diesel for both with and without PCM. The exhaust gases from the twin-cylinder four-stroke diesel engine without PCM contain 45.1% energy transferred to the atmosphere. The exhaust gases with a thermal energy storage system exchanging of heat to the PCM. The PCM stored thermal energy 5.5% of total energy from the exhaust during the charging process and reduced emission control by reducing energy transferred to the atmosphere form 45.1% to 39.5%. The thermal energy from the PCM discharged and used to generation of steam which can be used for different applications. The process without PCM gives more harmful gases and hazardous to humans and the environment, but the system with PCM gives minimum exhaust gas temperature which is minimum harmful to humans and the environment. The utilization of waste heat and its recovery reduces the fuel required to run the engine and lesser emission of greenhouse gases to the environment.